CORRELATION OF MEDICATION ADHERENCE WITH THE CHARACTERISTICS AND QUALITY OF LIFE OF TUBERCULOSIS PATIENTS IN DR. DRADJAT PRAWIRANEGARA HOSPITAL - Yusransyah Yusransyah; Rozwaliza Annintan; Farahdina Chairani; Baha Udin (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2023)
Tuberculosis remains a health threat in Indonesia because its prevalence is relatively high; therefore, special tuberculosis control is needed. One way to control tuberculosis is to increase compliance with treatment, which can affect quality of life. The main objective of this study was to determine the relationship between the level of treatment compliance and the characteristics and quality of life of patients at dr. Dradjat Prawiranegara Serang Hospital. This study used a cross-sectional, observational research method. Data were collected by distributing questionnaires filled out through direct interviews with the patients. The questionnaires used were the MARS and EQ-5D-5L questionnaires were used. The subjects in this study were outpatients with tuberculosis who were undergoing treatment at our hospital. The Drajat Prawiranegara Serang Hospital met the inclusion and exclusion criteria. Sequential sampling was used as a sampling technique in this study. Statistical data analysis was performed using the chi-square test and correlation. The number of respondents in this study who met the inclusion criteria was 30. As many as 80.0% of tuberculosis patients adhere to taking medication, and 83.3% of tuberculosis patients have a good quality of life. The results of statistical tests show that there is a relationship between the level of compliance of tuberculosis patients and the level of knowledge, income, attitude of health workers, and family support. In contrast, the variables of the level of education, employment, motivation, distance to health facilities, and quality of life did not have a significant relationship with the level of tuberculosis patient compliance...